Antimicrobial susceptibility pattern of pus culture in a tertiary care hospital of Jharkhand, India - Kumar, Rajiv; Kumar, Akhilesh; Keshri, Umashanker Prasad; Gari, Manju; Mahato, Sumit Kumar; Protim, Pholgu (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Antimicrobial resistance is developing day by day leading to increase not only in health care cost but also severity and death rate from certain infection that could have been avoided by rational use of existing and new antimicrobial agents. Present study is undertaken for this purpose to analyse the types of pathogens involved and their antibiotic sensitivity isolated from pus culture reports in a tertiary care hospital. Methods: Observational study was conducted using pus culture and sensitivity reports collected retrospectively from the records maintained in the Department of Microbiology over a period of 5 months from August 2016 to December 2016 in tertiary care hospital. Results: 85 percent pus samples were found culture positive of which microorganism isolated in decreasing order were Staphylococcus aureus, Pseudomonas, Klebsella and E. coli. Staphylococcus aureus was sensitive to fixed drug combination of piperacillin with tazobactam, linezolid, ceftriaxone with sulbactum, levofloxacillin and ciprofloxacin and resistance to cefotaxime, cloxacillin and ampicillin. Pseudomonas was highly sensitive to fixed drug combination of cefoperazone with sulbactum, piperacillin with tazobactum, ceftriaxone with sulbactum and resistance to cloxacillin and cefotaxime. Klebsiella showed high sensitivity to piperacillin with tazobactum, cefoperazone with sulbactum, ceftriaxone with sulbactum and was found resistant with norfloxacin and amoxycillin. E. coli showed high sensitivity in decreasing order with amikacin and gentamycin and resistance in increasing order with cefotaxime, cloxacillin, ampicillin and norfloxacin. Conclusions: The sensitivity patterns were different for each isolated microorganism but high sensitivity was found with fixed antimicrobial drug combination and resistance to frequently used drugs.